Lowering the C–H bond activation barrier of methane by means of SAC@Cu(111): periodic DFT investigations. (1st December 2021) - Bhati, Meema; Dhumal, Jignesh; Joshi, Kavita
Abstract : Methane has long been in the world's spotlight as the simplest yet one of the most notorious hydrocarbons; here, we study the efficiency of single-atom catalysts (SACs) for methane activation using density functional theory (DFT). Abstract : Methane has long captured the world's attention for being the simplest yet one of the most notorious hydrocarbons. Exploring its potential to be converted into value-added products has raised compelling interest. In the present work, we have studied the efficiency of single-atom catalysts (SACs) for methane activation employing density functional theory (DFT). The climbing image-nudged elastic band (CI-NEB) method is used in tandem with the improved dimer (ID) method to determine the minimum energy pathway for the first C–H bond dissociation of methane. Our study reported that the transition-metal doped Cu(111) surfaces enhance the adsorption, activate the C–H bond, and reduce the activation barrier for first C–H bond cleavage of methane. The results suggest Ru-/Co-/Rh-doped Cu(111) as promising candidates for methane activation with a minimal activation barrier and a less endothermic reaction. For these SACs, the calculated activation barriers for the first C–H bond cleavage are 0.17 eV, 0.24 eV, and 0.26 eV respectively, which is substantially lower than 1.13 eV, the activation barrier for Cu(111).